The Role of Internal Audit in Government Financial Management : An International Perspective - Diamond, Jack (IMF Working Papers; Working Paper ;, 2002)
The internal audit function has received increasing attention as an important component of government financial management and a tool for improving the performance of the government sector. Recently, a consensus has been reached on what audit standards governments should meet. This paper reviews these standards from an international perspective, noting that a large number of countries would face severe problems of meeting such standards. It is argued that internationally there are many different models for internal audit, and it may be necessary to take into account different audit traditions and different institutional capacities when introducing measures to strengthen internal audit in developing and transitional countries. The paper then discusses the main issues to be addressed in developing the internal audit in such countries, and offers a framework for introducing much needed reforms in this area.